New scoring system for differentiating xanthogranulomatous cholecystitis from gall bladder carcinoma: a tertiary care centre experience. Issue 1 (6th September 2016) - Rajaguru, Kishore; Mehrotra, Siddharth; Lalwani, Shailendra; Mangla, Vivek; Mehta, Naimish; Nundy, Samiran
Abstract : Background: Xanthogranulomatous cholecystitis (XGC) is an uncommon variant of chronic cholecystitis, characterized by a focal or diffuse destructive inflammatory process. The importance of XGC is that it mimics gall bladder carcinoma (GBC) both preoperatively and intra‐operatively, as it can present with pericholecystic infiltration, hepatic involvement and lymphadenopathy. As a result of a misdiagnosis, which is not infrequent, the patient may undergo an unnecessary radical cholecystectomy rather than only a cholecystectomy, which is associated with a greater morbidity and mortality. The main aim of the study is to formulate a simple preoperative scoring system for diagnosis of XGC which might benefit patients by avoiding radical procedures. Methods: A retrospective study was done from all the patients who underwent gall bladder and gall bladder‐related operations (benign and malignant), during a 5‐year time period from 2010 to 2014 in a tertiary care centre were reviewed ( n = 462). Results: Initial analyses of all the clinical and imaging parameters were done. Patients with a long history of recurrent abdominal pain with leucocytosis and who on imaging are found to have a diffusely thickened gall bladder wall, cholelithiasis, choledocholithiasis and submucosal hypoattenuated nodules are likely to have XGC while those with anorexia, weight loss, focal thickening of the gall bladder wall on imaging and dense local organ infiltration are more likely to have GBC. The presence of lymph nodes on imaging and the loss of a fat plane interface between the liver and gall bladder are not differentiating factors. A scoring system was made by taking statistically significant features ( n = 13) of clinical and imaging parameters in initial assessment to identify the features of XGC. The same scoring system was subsequently applied to the patients who underwent cholecystectomy to study the effectiveness and the results were reviewed. Conclusion: High value scores (≥11/13) helps in diagnosing XGC in preoperative setting. Hence, intra‐operative frozen section analysis can be avoided in such cases to differentiate XGC and GBC. However in difficult cases with high suspicion of malignancy based on clinical experience, definitive diagnosis still remains a histopathological examination to avoid radical resection in patients who have a benign condition.